Diagnostic study of explosive cyclogenesis during FGGE - Wash, Carlyle H.; Peak, James E.; Calland, Wynn E.; Cook, William A. (1988)
The article of record as published may be found at http://dx.doi.org/10.1175/1520-0493(1988)116<0431:DSOECD>2.0.CO;2 Two rapidly developing extratropical maritime cyclones (one, developed during January 13-15, 1979, along an intense frontal zone south of Japan, the other, of January 26-27, 1979, in a polar mass over the North Atlantic) were investigated using the FGGE data and ECMWF level IIIb analyses to describe the structure and dynamics of these events. Although the cyclones evolved from a strong low-level baroclinic zone without initial large midtropospheric vorticity advection, thus resembling the Petterssen type A development, rapid deepening occurred in both cases when an approaching upper tropospheric jet with appreciable shear vorticity advection became favorably superposed over the surface low. During the development period, stability decreased in the low troposphere, aiding in the rapid development of an intense mass-circulation and low tropospheric vorticity production by the divergence term. The results suggest that upper-level forcing plays a greater role in the initiation of explosive oceanic development than is suggested by the Petterssen and Smebye (1971) description. Approved for public release; distribution is unlimited.